2020
DOI: 10.1186/s12870-020-02465-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of rhizosphere soil of different allelopathic potential rice accessions

Abstract: Background: Identification of the allelopathy-interrelated metabolites from the allelopathic rice rhizosphere is crucial to understand the allelopathic mechanism of rice, which in turn can promote its applications to farming. In this study, the metabolites from the rhizosphere soil of five different rice lines, including allelopathic rice accession PI312777 (PI) and non-allelopathic rice accession Lemont (Le) as well as their genetic derivatives (e.g., phenylalanine ammonia-lyase (PAL) gene overexpression tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…These rhizosphere metabolites likely consist of a large fraction of the plant exudates, microbial products, and background C compounds present in the bulk soil. A number of studies have analyzed metabolites present in rhizosphere soil of maize, Arabidopsis, wheat, rice, wild oat (13,(83)(84)(85)(86). However few studies have identified changes of rhizosphere metabolites in soil in response to abiotic stressors.…”
Section: Exometabolites Reflect Rhizosphere Abiotic Stress Conditionsmentioning
confidence: 99%
“…These rhizosphere metabolites likely consist of a large fraction of the plant exudates, microbial products, and background C compounds present in the bulk soil. A number of studies have analyzed metabolites present in rhizosphere soil of maize, Arabidopsis, wheat, rice, wild oat (13,(83)(84)(85)(86). However few studies have identified changes of rhizosphere metabolites in soil in response to abiotic stressors.…”
Section: Exometabolites Reflect Rhizosphere Abiotic Stress Conditionsmentioning
confidence: 99%
“…For example, exudates collected in deionized water often contained higher levels of carbon and amino acids 15,21,22 , likely due to the strong osmotic imbalance between root and solvent. Exudate collection duration also influences the metabolic profile 15,23 Few studies analyzed exudates from soil-grown plants, which is usually done with spatial resolution using membranes or leachate collection , or by washing pots with water or organic solvent 24,25 . The presence of microbes in nonsterile settings or of a soil matrix leads to the detection of a complex metabolite profile.…”
Section: Introductionmentioning
confidence: 99%
“…Because of major technical advancements in mass spectrometry, we now know a great deal about root exudate composition in model species such as Arabidopsis [ 127 , 128 , 129 ], maize [ 130 ], and rice [ 131 , 132 ] and their effects on associated microbiota [ 133 , 134 , 135 ]. Today, there are still a small number of examples of metabolomics being applied to study root exudates in either field [ 136 , 137 ] or greenhouse soils [ 138 , 139 ]; however, recent experimental advancements promise to address challenges related to non-sterile soil matrices [ 140 ].…”
Section: From Genes To Ecosystems: Studying Plant–microbe Interaction...mentioning
confidence: 99%